What Is the Proper Role for Charity in Healthcare? - Ackerman, Felicia (Cambridge quarterly of healthcare ethics, 1996)
My little girl has leukemia; she has had it for over a year, and now she needs at least five pints of blood a day. Not the whole blood, just the platelets. Most of our relatives and friends have given at least a few times. But we need more. Now I have to go to strangers.So begins Roberta Silman's short story, “Giving Blood,” a story about illness and charity. When the narrator's husband solicited blood donations at his workplace, “he thought everyone would help…He must have asked a hundred people. Thirty gave. His officemate…turned green and said, ‘Oh, no, anything but that. I'm scared of needles.'”